Global distribution an characteristics of black soils - Angelini, Marcos Esteban; Rodriguez, Dario Martin; De La Fuente, Juan Carlos; Tenti Vuegen, Leonardo Mauricio; Moretti, Lucas Martin; Schulz, Guillermo; Fontana, Ademir; Landi, Ahmad; Mermut, Ahmet R.; Moreira, Ana Laura; Morras, Hector (FAO, 2022)
Although “black soils” is a term used in some national soil classifications, which is influenced by the national linguistic specifics, there has been no consistent definition for black soils at the global level. In the WRB classification (IUSS Working Group WRB, 2015), the majority of black soils would correspond to Chernozems, Kastanozems and Phaeozems. Hovewer, other groups such as Vertisols, Fluvisols, cambisolos and Anthrosols may fit the definition of black soils. In correspond to the Mollisols Great Order according to the United States of America Soil Taxonomy (USDA, 2014). Many other regional variants exist, such as in China, where the original name for these soils was “black soils”, and they are now classified as “Isohumisols” in Chinese Soil Taxonomy. In Ukraine, these soil types are included in a group characterized a humus-accumulative type of soil formation, which is a great group of the Chernozems, assimilated to Russian Federation black soils or “black earths”. The harmonization of the definition of black soils is required to facilitate their sustainable management and international technical exchanges. In 2019, FAO and its advisory body, the Intergovernmental Technical Panel on Soils (ITPS), endorsed the definition of black soils as “black soils are mineral soils which have a black surface horizon, enriched with organic carbon that is at least 25 cm deep” (FAO, 2019). Two categories of black soils (1st and 2nd categories) are recognized. The categories are distinguished to recognize the higher value, and thus greater need for protection, of some soils (Category 1), while still including a wider range of soils within the overall black soil definition (Category 2). The 1st category of black soils (the most vulnerable and endangered, needing the highest rate of protection at a global level) are those having all five properties given below: 1. The presence of black or very dark surface horizons typically with a chroma of ≤3 moist, a value of ≤3 moist and ≤5 dry (by Munsell colours); 2. The total thickness of black surface horizons ≥25 cm; 3. Organic carbon content in the upper 25 cm of the black horizons of ≥1.2 percent (or ≥ 0.6 percent for tropical regions) and ≤20 percent; surface horizons ≥25 cmol/kg; and 5. A base saturation in the black surface horizons ≥ 50 percent. Most, but not all, 1st category black soils have a welldeveloped granular or fine sub-angular structure and high aggregate stability in the black surface horizons that are in a non or slightly degraded state, or in the humus-rich underlying horizon which has not been subjected to degradation. The 2nd category of black soils (mostly endangered at the national level) are those having all three properties given below: 1. The presence of black or very dark surface horizons typically with a chroma of ≤3 moist, a value of ≤3 moist and ≤5 dry (by Munsell colours); 2. The total thickness of the black surface horizons of ≥25 cm; and 3. Organic carbon content in the upper 25 cm of the black horizons ≥ 1.2 percent (or ≥ 0.6 percent for tropical regions) and ≤ 20 percent.